In vitro antioxidant and anti-neoplastic activities of Ocimum sanctum leaves in Ehrlich Ascites Carcinoma bearing mice - Islam, M. Saiful; Alam, M. Badrul; Zahan, Ronok; Sarker, G.C.; Chowdhury, N.S.; Khan, M. Maruf; Hasan, Mahedi; Rahman, M. Saifur; Mosaddik, M.A.; Jesmin, Mele; Haque, M. Ekramul (© 2011 Academic Journals Inc., 2016)
This article was published in International Journal of Cancer Research [© 2011 International Journal of Cancer Research] and the definite version is available at: http://docsdrive.com/pdfs/academicjournals/ijcr/0000/29556-29556.pdf The article website is at: http://scialert.net/abstract/?doi=ijcr.2011.209.221